AUTOIMMUNE MYOCARDITIS: PERIPHERAL BLOOD ARCHITECTONICS AND CLINICAL COURSE FEATURES - Z. S. Shogenov; K. A. Akhmedilova; N. N. Kekenadze; M. M. Agirov; O. A. Pronina; B. V. Pinegin; T. Elbeik; L. S. Metelitsa; S. B. Suchkov; P. Kh. Dzhanashiya (Российский кардиологический журнал)
.